Antecedents of hospital admission for deliberate self-harm from a 14-year follow-up study using data-linkage - Mitrou, F.; Gaudie, J.; Lawrence, David; Silburn, Sven; Stanley, F.; Zubrick, Stephen (BioMed Central Ltd., 2010)
Antecedents of hospital admission for deliberate self-harm from a 14-year follow-up study using data-linkageFrancis Mitrou1 email, Jennifer Gaudie1 email, David Lawrence1,2 email, Sven R Silburn1,2 email, Fiona J Stanley1 email and Stephen R Zubrick1,2 email1 Telethon Institute for Child Health Research, Centre for Child Health Research, The University of Western Australia. PO Box 855, West Perth, WA. 6872, Australia2 Centre for Developmental Health, Curtin Health Innovation Research Institute, Curtin University of Technology, Perth, Western Australia, Australiaauthor email corresponding author emailBMC Psychiatry 2010, 10:82doi:10.1186/1471-244X-10-82The electronic version of this article is the complete one and can be found online at: http://www.biomedcentral.com/1471-244X/10/82Received: 22 April 2010Accepted: 18 October 2010Published: 18 October 2010© 2010 Mitrou et al; licensee BioMed Central Ltd.This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.